Sex and some environmental factors effects on birth weight of Nelore Calves - Ferreira, Paulo Roberto Costa; Viana, Hildo Áurio (Pesquisa Agropecuaria Brasileira, 2014)
Birth weight of 1,372 Nelore calves born from 1975 to 1980 from cows between the 1st and 10th parity was analysed using the Stepwise Method of multiple regression analysis. Four variables were selected (P<0.01): Sex of calf, year and month of birth, and calving parity of dam. The average birth weight was 29.01 ± 2.58 kg. Male calves were 0.90 kg heavier than females. Year of birth determined a guadratic curve with minimum in 1976. Age of dam influenced birthweight in a guadratic way, with a maximum in the 5th and 6th parity. Month of birth determined a cubic curve, with a maximum weight for animals born on March/Abril and a minimum for those born on July/August. Nutrition and reproductive management seemed to explain these results.